Urdu ka guldasta Nargis - Fauzia Ehsan Farooqi (Karachi; Oxford University Press., 2022)
**Abstract of *Urdu Ka Guldasta Nargis*** Urdu Ka Guldasta Nargis* is an engaging Urdu language textbook that offers a blend of classical and modern prose, poetry, and stories to help students strengthen their command of the Urdu language. The book is designed to develop core language skills, including reading comprehension, writing, vocabulary, and grammar. With a focus on cultural appreciation and literary exploration, each lesson encourages students to think critically and creatively while enhancing their understanding of Urdu literature. The exercises and activities promote language proficiency, making it a valuable resource for students to deepen their connection with the richness of Urdu.